An exploration of pharmacist-patient communication in clinic-style consultations - Greenhill, Nicola H. (2010)
The importance of communication skills for pharmacists has been widely acknowledged. Research has shown that the use of good communication skills can improve patient health outcomes but little research has focussed on communication within new consultation based roles of pharmacists. This study aimed to explore the communication between pharmacists and patients in clinic style consultations and to investigate participant perceptions of communication and consultations.